Alternatif Perencanaan Struktur Gedung UNIMUDA Hospital Sorong 5 Lantai pada Wilayah Gempa 4 - Angga Puji Triono; Andi Rahmat; Elfiyusriningsi Syara (CV. Shofanah Media Berkah, 2025)
To plan a high-rise building structure that is safe from earthquake disasters, at least the structure must have good strength and behavior.UNIMUDA Sorong Hospital building structure planning aims to use steel materials to design buildings that are resistant to earthquake loads in accordance with the Indonesian National Standard (SNI), and can plan the dimensions of beams and columns that are strong to withstand earthquake loads based on the Indonesian National Standard (SNI). Loading calculations and analyzes are carried out with the help of the SAP 2000 v14 program. The structure is designed using a Special Moment Bearing Steel Frame System with seismicity factor using dynamic response spectrum. With a fundamental period of 0.8228 seconds. The maximum fundamental period is 1.1134 seconds, and the deviation value between non-existent floors exceeds the maximum deviation limit of 30.769 mm. Beam 1 is designed with an IWF of 400 x 200 x 8 x 13 using an additional stiffener plate having a Vu value of 212 367.77 N; φVn = 590 400 N; Mu = 359 578 346 Nmm and φMn = 463 198 437 Nmm. Beam 2 is designed with an IWF of 400 x 200 x 8 x 13 without body stiffeners having a Vu value of 163 492 N; φVn = 590 400 N; Mu = 278 327 523 Nmm and φMn = 463 198 437 Nmm. Effective steel columns in this structure use WF 400 x 400 x 21 x 13 with Pu value of 2162478.73 N, φVn = 678 600 N. Mux = 112561292.5, Muy = 78189223.26 Nmm and φMnx = 769 813 060 Nmm , φMny = 188770276 Nmm . This indicates that the column is secure.